Long‐term results of a randomized study comparing parathyroidectomy with cinacalcet for treating tertiary hyperparathyroidism. Issue 8 (3rd June 2020) - Moreno, Pablo; Coloma, Ana; Torregrosa, José V.; Montero, Nuria; Francos, José; Codina, Sergi; Manonelles, Anna; Bestard, Oriol; García‐Barrasa, Arantxa; Melilli, Edoardo; Cruzado, Josep M.
Abstract: Tertiary hyperparathyroidism is a common cause of hypercalcemia after kidney transplantation (KT) and has been associated with renal dysfunction, bone mineral density loss, and increased risk of fracture and cardiovascular events. In a previous 12‐month clinical trial, we demonstrated that subtotal parathyroidectomy was more effective than cinacalcet for controlling hypercalcemia. In the current study, we retrospectively evaluate whether this effect is maintained after 5 years of follow‐up. In total, 24 patients had data available at 5 years, 13 in the cinacalcet group and 11 in the parathyroidectomy group. At 5 years, 7 of 11 patients (64%) in the parathyroidectomy group and 6 of 13 patients (46%) in the cinacalcet group ( P  = .44) showed normocalcemia. However, recurrence of hypercalcemia was only observed in the cinacalcet group ( P  = .016). Subtotal parathyroidectomy retained a greater reduction in intact parathyroid hormone (iPTH) compared with cinacalcet group. No differences were observed in kidney function and incidence of fragility fractures between both groups. Cinacalcet was discontinued in 5 out of 13 patients. In conclusion, in kidney transplant patients with tertiary hyperparathyroidism recurrence of hypercalcemia after 5‐year follow‐up is more frequent in cinacalcet than after subtotal parathyroidectomy.